Alternatif Penyelesaian Sengketa Waris Oleh Dalihan Na Tolu Di Desa Lumban Dolok Kecamatan Siabu - Ilham Syukur (Jurnal El-Thawalib, 2022)
This study examines the role of Dalihan Na Tolu in the settlement of inheritance disputes in Lumban Dolok Village, Siabu District, Mandailing Natal Regency. This research is a field research with a qualitative approach using primary data, namely data obtained directly from Dalihan Na Tolu, and the people of Lumban Dolok Village, especially people who have litigation. Meanwhile, secondary data was obtained by reviewing books, journals, and documents related to this research. Data collection in this study used the methods of observation, interviews, and documentation. The data analysis technique used descriptive qualitative analysis method. The results of this study that the concept of kinship between individuals in the Lumban Dolok Village community is reflected in the Dalihan Na tolu concept, there are several causes that cause disputes in the Lumban Dolok Village community, namely the lack of knowledge of the Lumban Dolok Village community regarding inheritance. Meanwhile, in the settlement of inheritance disputes, Dalihan Na Tolu acts as a mediator and acts as a facilitator. Furthermore, Dalihan Na Tolu has a strong reason so that Dalihan Na Tolu participates in the settlement of inheritance disputes, namely holding the principle of togetherness, feeling the same fate, being heavy and carrying, light and carrying. The settlement of inheritance disputes by non-litigation method is mostly successful and rarely is this inheritance problem brought to court if it has been resolved first by Dalihan Na Tolu.